2008
DOI: 10.1007/s12144-008-9027-9
|View full text |Cite
|
Sign up to set email alerts
|

Person–Situation Interaction in Adaptive Emotional Functioning

Abstract: Two studies applied a person-situation model to examine the effect of emotional affordances of situations. Participants rated their emotional functioning as more extensive in situations classified as being high in emotional affordance than those classified as low in emotional affordance. Participants who scored higher on the individual difference characteristic of emotional intelligence were more interested in entering high emotional affordance situations than were individuals lower in emotional intelligence, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 12 publications
3
22
0
Order By: Relevance
“…The results of the present study support the importance of developing individuals' emotional intelligence in order to enhance their career adaptability. The results of the present study corroborate previous studies (Brown et al, 2003;Coetzee & Beukes, 2010;Schutte et al, 2008) which indicate emotional intelligence to be predictive of career decision-making self-efficacy, and vocational exploration and commitment. Overall, the results of the present study provide evidence that high levels of self-efficacious emotional functioning may enhance self-efficacious adaptive functioning in the cognitive-affective behavioral domains of career adaptability.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The results of the present study support the importance of developing individuals' emotional intelligence in order to enhance their career adaptability. The results of the present study corroborate previous studies (Brown et al, 2003;Coetzee & Beukes, 2010;Schutte et al, 2008) which indicate emotional intelligence to be predictive of career decision-making self-efficacy, and vocational exploration and commitment. Overall, the results of the present study provide evidence that high levels of self-efficacious emotional functioning may enhance self-efficacious adaptive functioning in the cognitive-affective behavioral domains of career adaptability.…”
Section: Discussionsupporting
confidence: 91%
“…Managing one's own emotions refers to a sense of emotional self-efficacy, including confidence in the ability to control one's personal emotions, using positive mood to persevere in spite of obstacles and motivate the self to achieve success (Schutte et al, 2009). Emotional self-efficacious functioning has been shown to be important for engaging in problem-solving behaviors and dealing positively with career-related challenges (Brown et al, 2003;Coetzee & Beukes, 2010;Schutte et al, 2008). The results of the present study also indicated the ability of managing one's own emotions and having high levels of career concern as two important psychosocial career metacapacities in predicting career adaptability.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations